Potato yield and soil physical properties as affected by subsoiling - Holmkvist, Anna (2008)
Agriculture practices today include the use of heavy machinery which leads to soil compaction. High soil strengths are known to restrict the root development and prevent root growth. Sandy soils, which often are used in potato production, seem to be especially susceptible to subsoil compaction. Subsoiling is a way to loosen up the plough pan by deeper tillage. General it decreases soil strength and bulk density, the effect is that the roots can penetrate further down in the soil which may reduce stress caused by inadequate water and nutrient supply. The persistence of subsoiling is dependent on several factors such as soil moisture at the time of subsoiling, the choice of subsoiling equipment and traffic practices following the subsoiling. The best way to prevent recompaction is to apply controlled wheel traffic. The conclusion from my literature study is that under near optimum irrigation levels subsoiling are of no benefit to the yield but during more drought conditions the additional rooting volume significantly increase potato yields, but have no effect on the quality. Therefore subsoiling can be of importance in areas were irrigation is not used.